EX VIVO ASSESSMENT OF RIGHT VENTRICULAR HEMODYNAMICS UNDER TRICUSPID VALVE INTERACTION AND APPLICATIONS IN EVALUATING TREATMENTS FOR SEVERE FUNCTIONAL TRICUSPID REGURGITATION - NGUYEN YEN NGOC (2020)
Ph.D